Handgrip Strength Prediction Formula Using Aneroid Sphygmomanometer in Elderly - Akhmad Yahin; Marina Annette Moeliono; Marietta Shanti Prananta (International Journal of Integrated Health Sciences, 2016)
Objective: To examine the prediction formula used to measure handgrip strength using aneroid sphygmomanometer in elderly.Methods: This study was a cross-sectional study performed at the Department of Physical Medicine and Rehabilitation, Faculty of Medicine, Universitas Padjadjaran-Dr. Hasan Sadikin General Hospital from March to April 2015. Thirty five elderly subjects aged 60–74 years were included in the study. The subject handgrip strength was measured using an aneroid sphygmomanometer and a Jamar dynamometer. Results: All data were analyzed statistically using Pearson correlation test to examine the distributed data and Spearman test to examine the non distributed data. A significant correlation was found between hand width, age, and sex and the handgrip strength values using Jamar dynamometer (p<0.01) using multiple linear regression (p<0.01). A normality test using the Shapiro-Wilk test resulted normal residue with p value 0.000. The results showed that the regression analysis could be used to predict the handgrip strength using aneroid sphygmomanometer.Conclusions: Aneroid sphygmomanometer can be used to predict handgrip strength in elderly using conversion formula. Keywords: Aneroid sphygmomanometer, elderly, handgrip strength, Jamar dynamometer DOI: 10.15850/ijihs.v4n2.832